PROFITABILITY OF ZERO TILL MAIZE INFLUENCED BY NUTRIENT AND WEED MANAGEMENT PRACTICES - SURENDRA BABU. P; NARENDER REDDY. S, NAGANJALI. K, VANI. K. P, MADHAVI. M (The Journal of Research, PJTSAU, 2023)
Field experiment was carried out at College Farm, Agricultural College, Aswaraopet, Professor Jayashankar Telangana State Agricultural University, during rabi 2016-17 and 2017-18 with three nutrient management (M1: 100% RDF, M2: 75% RDF +25% N through Vermicompost and M3: 75% RDF + 25% N through FYM) and four weed management treatments (S1: Control; S2: Atrazine 50 WP 500 g ha-1 + Paraquat 24 SL 0.6 kg ha-1 fb 2,4 - D 0.5 kg ha-1 at 25 DAS; S3: Atrazine 50 WP 500 g ha-1 fb (Topramezone 0.03 kg ha-1 + Atrazine 50 WP 500 g ha-1) at 25 DAS and S4: Topramezone 0.03 kg ha-1 + Atrazine 50 WP 500 g ha-1 at 15 DAS fb HW at 35 DAS) in both the years. Among nutrient management practices, highest total number of grains cob-1 (313.76, 324.38), test weight (21.97, 22.44 g), grain yield (5399, 5766 kg ha-1) and straw yield (6674, 7041 kg ha-1) were recorded with 75% RDF + 25% N through Vermicompost (M2) and at par with 75% RDF + 25% N through FYM (M3) during rabi 2016-17 and 2017-18 respectively. Out of weed management treatments tested, highest total number of grains cob-1 (365.26, 378.62), test weight (22.06, 22.54 g), grain yield (6275, 6708 kg ha-1) and straw yield (7475 and 7908 kg ha-1) were observed with Topramezone 0.03 kg ha-1 + Atrazine 50 WP 500 g ha-1 at 15 DAS fb HW at 35 DAS S4 and comparable with S3 Atrazine 50 WP 500 g ha-1 fb (Topramezone 0.03 kg ha-1 + Atrazine 50 WP 500 g ha-1) at 25 DAS during rabi 2016-17 and 2017-18 respectively. Under various nutrient treatments, significantly 75% RDF + 25% N through Vermicompost (M2) fetched higher net returns (47882, 53424 ha-1) while B:C ratio (2.42, 2.59) was maximum with 75% RDF + 25% N through FYM (M3) in two successive years respectively. Amongst weed management practices, significantly higher net returns (61282, 67886 ha-1) were obtained with S4 (Topramezone 0.03 kg ha-1 + Atrazine 50 WP 500 g ha-1 at 15 DAS fb HW at 35 DAS) and B:C ratio (2.76, 2.95) was realized with S3 Atrazine 50 WP 500 g ha-1 fb (Topramezone 0.03 kg ha-1 + Atrazine 50 WP 500 g ha-1) at 25 DAS in rabi 2016-17 and 2017-18 respectively.